Pengaruh Edukasi Dengan Audio Visual Terhadap Pengetahuan Ibu Tentang Stunting Desa Teluti Baru Tahun 2023 - Maritje S.J Malisngorar; Ety Dusra; Siti Nadya Silawane (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2025)
Stunting is a condition of growth failure that occurs in children under five years of age (bavi under five years) as a result of chronic malnutrition so that children look short at their age. Stunting occurs in the critical period from the womb, 1000 HPK to the age of two years. if not addressed it will have a permanent impact because stunting is irreversible or cannot be corrected. This study is to determine the effect of education with audio visual media on mothers' knowledge about stunting in Telutih Baru Village, Tehoru District.This study used Pre-Experiment method with one group pre-test and post-test design. The population in this study were 45 mothers who had a 2-year-old bailta. While the sample in this research is 45 mothers who have toddlers aged 2 years in Teluti Baru Village, Tehoru District. The sampling technique used total sampling technique The research instrument used a questionnaire in the form of statements, the variable in this study was a single variable, namely maternal knowledge. The analysis used in this study was the Wilcoxon Test.analysis of the effect of education with Audio Visual media on maternal knowledge about stunting in Teluti Baru Village, Tehoru District in 2023 from the results of the Wilcoxon Test Respondents' knowledge decreased 0, knowledge remained 0, Respondents' knowledge increased 45.